The effect of the Agulhas Current on synthetic aperture radar derived wind fields - Schilperoort, Daniel E (Department of Oceanography, 2017)
In this study, 5 years (987 swaths) of high resolution wind speeds, derived from Advanced Synthetic Aperture Radar data collected over the Agulhas Current region, are studied to investigate the effect of warm, high intensity currents on the ocean's surface roughness and resulting derived wind fields. The wind data are derived using the CMOD5.n GMF with CFS reanalysis wind data as direction input. The CFS direction data are validated using ASCAT derived wind observations Globcurrent ocean current velocity data is used to investigate the difference between the satellite derived wind speeds compared to surface velocities of the current and the true wind speed. The, so called, current-relative effect is investigated for different wind direction regimes, namely: upcurrent, downcurrent, crosscurrent west and crosscurrent east. Our analyses are conducted for 6 locations of interest, evenly spaced along the Northern Agulhas Current. MODIS, SEVIRI and OSTIA SST data are used as proxy for locating the core of the Agulhas and it's temperature fronts, as well as to investigate wind speed modifications as a result of ocean-atmosphere energy transfer. It is found that higher resolution SAR derived winds have a greater ability to represent higher intensity and smaller scale wind features in comparison to winds derived from Scatterometers. A combination of the current relative effect and SST-atmospheric heating for upcurrent wind directions results in a sharp increase in mean wind speeds over the inshore boundary of the current of between 5m/s and 7m/s (50−60%). Individual events can reach as high as 15m/s (100%) over 10′s of kilometres. For downcurrent winds, the expected current relative effect is overridden by increased wind speeds of up to 5m/s (40%) across the entire current due to the influence of SSTs. The mean effect of SSTs on wind speeds has a stronger effect than the current relative effect on wind speed changes over the current. The wind speed differences are best represented under moderate wind speeds, between 5−15m/s. This investigation will contribute to future satellite wind speed derivations to identifying new wind speed and surface roughness altering effects. It will also serve to increase understanding of high resolution wind features and sharp changes over ocean features.